2014
DOI: 10.1186/1471-5945-14-12
|View full text |Cite
|
Sign up to set email alerts
|

Two sisters reveal autosomal recessive inheritance of epidermodysplasia verruciformis: a case report

Abstract: BackgroundEpidermodysplasia verruciformis is a rare genodermatosis characterized by a unique susceptibility to cutaneous human papillomaviruses infection. Most patients show autosomal recessive patterns of inheritance.Case presentationWe report a case of two sisters with clinically epidermodysplasia verruciformis specific lesions on the face, neck, trunk, and extremities. PCR analysis indicated the presence of human papillomavirus type 5 in the lesions. Electron microscopic examination showed viral-like partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
0
10
0
4
Order By: Relevance
“…There are more than 30 EV-associated HPV types that have been recognized, including HPV5, HPV8, HPV12, HPV14, HPV15, HPV17, HPV19-HPV25, HPV36, HPV38, HPV47, and HPV50 [4]. Malignant transformations are primarily caused by HPV5 and HPV8 [9]. A young woman presented with a left infraorbital lesion that revealed squamous cell carcinoma [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are more than 30 EV-associated HPV types that have been recognized, including HPV5, HPV8, HPV12, HPV14, HPV15, HPV17, HPV19-HPV25, HPV36, HPV38, HPV47, and HPV50 [4]. Malignant transformations are primarily caused by HPV5 and HPV8 [9]. A young woman presented with a left infraorbital lesion that revealed squamous cell carcinoma [1].…”
Section: Discussionmentioning
confidence: 99%
“…Presently, acitretin 0.5-1 mg/day is the drug of choice [ 3 ]. Oral retinoids (0.5 mg/kg) used in two sisters with an autosomal recessive pattern showed that cutaneous lesions decreased in size after a short time but a relapse of the lesions occurred after one year [ 9 ]. A surgical approach, including electrosurgical removal and cryotherapy, is also used to manage benign and premalignant lesions [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous, invalidating mutations in either the TMC8 or TMC6 gene are found in approximately 75% of epidermodysplasia verruciformis patients and confer susceptibility to the disease ( Orth, 2006 , Ramoz et al., 1999 , Ramoz et al., 2002 ). Most patients demonstrate autosomal recessive patterns of inheritance, although some exhibit X-linked recessive or autosomal dominant inheritance ( Yoshida et al., 2014 ).…”
Section: Case Presentationmentioning
confidence: 99%
“…¥ Khalili et al., 2014 . £ Yoshida et al., 2014 . AD: autosome dominant; AR: autosome recessive; BuLoc: nucleotide changes; CAG: congenital agammaglobulinemia; DCFHR: deficiency in complement factor H-related protein; del: deletion; EDV: epidermodysplasia verruciformis; FreNor: mutation frequency in normal individuals; Het: heterozygote; Hom: homozygote; IFD: invasive fungal disease; Inh: inheritance; NoTra: number of transcripts; PID: primary immunodeficiency.…”
Section: Case Presentationmentioning
confidence: 99%
“…A more aggressive course may occur in association with other risk factors, such as ultraviolet radiation [5,10]. Mental disorders, such as cognitive impairment, can be seen in about 10% of the cases [1,3,7,8].…”
Section: Introductionmentioning
confidence: 99%